DETERMINANTS OF THE LACK OF INTEREST IN CULTIVATING MEDICINAL PLANTS IN WONOGIRI, CENTRAL JAVA - M Bakti Samsu Adi; Devi Safrina; Slamet Wahyono (Balai Besar Penelitian dan Pengembangan Tanaman Obat dan Obat Tradisional, 2022)
Indonesia is among the countries producing medicinal plants for domestic and foreign demand. Nevertheless, Indonesia keeps importing a variety of medicinal plant kinds. One reason for this is farmer's lack of interest in cultivating medicinal plants, which is interesting to observe considering that, in terms of market share, ecology, and geography, all of them support the development of medicinal plant cultivation. This cross-sectional study with observations and interviews aims to get primary data to identify the factors causing the lacking interest of farmers in cultivating medicinal plants. In October 2018, we conducted our data collection. Statistics Indonesia (BPS) provided secondary data on the production and trade of medicinal plants from 2009 to 2020. We did descriptive data analysis. The results showed several factors caused farmers to be less interested in cultivating medicinal plants. Expense fluctuations, the length of the planting period, technology, and access to marketing, until the government's attention has not been optimized are the contributing factors. It should make efforts to increase the interest of farmers in cultivating medicinal plants. There are ways to encourage people to grow medicinal plants as their primary source of income, including stable prices, market accessibility, efficient cultivation, and post-harvest technology.